Futureland - Nuno Cera this exhibition, produced by the EDP Foundation, constitute part of the Associate Projects of the Lisbon Architecture Triennale, 2010 - Cera, Nuno 1972- (Athena, é uma chancela Babel, 2010)
Futureland is the name for Nuno Cera's most recent project, which deals with the issue of the impact of urban growth on people and on the environment, as well as with the connection between architecture, the public space and society. It is divided into three forms of presentation: video installation, a series of photographs and a catalogue